Governance and Dynamic Efficiency with Network Structure in the Brazilian Natural Gas Utilities - Francisco Roldineli Varela Marques; Alexandro Barbosa; Pedro Simões; Kelly Cristina de Oliveira (Applied Sciences)
The objective of this work is to analyze the relevance of governance (corporate and ownership concentration) for the divisional inter-temporal dynamic efficiency in piped natural gas utilities in Brazil. The main innovative contribution of this work is the application of inter-temporal (dynamic) efficiency analysis with network structure in the first stage, in this case, the ‘Dynamic DEA (Data Envelopment Analysis) with network structure: A slacks-based–DNSBM (Dynamic Network Slacks-Based Measure)’, in which two divisional interactions <semantics><msubsup>δok∗</msubsup></semantics> (technical–operational and economic–financial division) between <semantics><msubsup>τot∗</msubsup></semantics> periods and divisional <semantics><msubsup>ρokt∗</msubsup></semantics> periods are reflected in the overall efficiency scores <semantics><msubsup>θo∗</msubsup></semantics>, representing an approach not yet explored by the previous literature on the sector and subject investigated. The database used corresponds to 21 Brazilian natural gas utilities in the form of a balanced data panel, which were collected for the period 2014–2019. The second stage (explanatory) was estimated through the panel with random effects to identify the relationship between governance and efficiency, considering certain context factors. The results show that the average general efficiency was 74.96%, resulting from the interactions between the average efficiency rates of 72.21% of the technical–operational division and 82.03% of the economic–financial division, and suggest that the corporate governance index and ownership (public or private) are not relevant factors for the efficiency results studied.